Tubocapsenolide A targets C-terminal cysteine residues of HSP90 to exert the anti-tumor effect. (April 2021) - Zhu, Dongrong; Li, Shang; Chen, Chen; Wang, Sibei; Zhu, Jiangmin; Kong, Lingyi; Luo, Jianguang
Abstract: Heat shock protein 90 (HSP90) is a chaperone protein that has been shown to regulate cancer progression. As a result, HSP90 has emerged as an attractive target for cancer therapy. Tubocapsenolide A (TA) is an anti-tumor component isolated from Tubocapsicum anomalum . Although the anti-tumor activity of TA was considered to be related to HSP90, the binding site and deep anti-tumor mechanisms still need to be elucidated. In this study, we found that TA is a covalent inhibitor of HSP90, which inhibits HSP90 ATPase activity without blocking ATP binding. Further studies indicated that TA targets the C-terminal Cys521 site, which led to HSP90 partial oligomerization and hindered its anti-aggregation and refolding activity. The damage of the chaperone activity disrupted the interaction between HSP90 and its cochaperone CDC37 as well as its client proteins, thereby inducing cell cycle arrest and apoptosis. Moreover, TA was found to have therapeutic effects on the xenograft tumor model by inducing the degradation of HSP90 client proteins. Together, our results identified HSP90 as the direct target of TA for mediating the anti-tumor activity. TA could serve as a lead compound for developing novel HSP90 C-terminal covalent inhibitors with binding site different from the ATP-binding domain. Graphical Abstract: ga1 Highlights: TA disrupts the interaction of HSP90/CDC37 and HSP90/client proteins. The α, β – unsaturated ketone unit is the pharmacophore of TA. TA covalently binds to HSP90 and hinders its chaperone activity. TA inhibits HSP90 ATPase activity without blocking ATP binding. Cys521 of HSP90 is more important than Cys564 for the anti-tumor effect of TA.